2011
DOI: 10.1136/emj.2010.106229
|View full text |Cite
|
Sign up to set email alerts
|

Medical problems presenting to paediatric emergency departments: 10 years on

Abstract: Over a 10-year period, there has been a rise in the number of people attending the ED with medical conditions. The 10 most common presenting problems account for 85% of medical attendees. These results suggest the increasing utilisation of ED services for children with common medical presenting problems and should inform further research exploring the pathways for attendance and the thresholds in seeking medical advice in order to inform the commissioning of paediatric emergency and urgent care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 8 publications
(2 reference statements)
1
104
1
Order By: Relevance
“…1 In young children presenting with an acute febrile illness, serious bacterial infection occurs in ∼7%. Bacteremia occurs in 1 in 250 febrile children aged ,5 years and may be difficult to recognize.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
“…1 In young children presenting with an acute febrile illness, serious bacterial infection occurs in ∼7%. Bacteremia occurs in 1 in 250 febrile children aged ,5 years and may be difficult to recognize.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
“…It is difficult to be certain; indices of quality in paediatric primary care are scant 8 but several studies have identified areas where improvement is required. These include the timely recognition of childhood cancers, management of chronic conditions, 9 and reducing the number of children presenting to accident and emergency departments 10 or admitted to hospital. 11 Perhaps of greatest concern is that the 2008 Confidential Enquiry into Maternal and Child Health 12 identified failure to recognise serious illness by healthcare staff not trained in paediatrics as a recurring factor in childhood deaths.…”
Section: Attempts To Address the Deficitmentioning
confidence: 99%
“…In comparison to other countries, there is paucity of Swiss data in the published literature on the distribution of presenting medical and surgical complaints in children who visit a paediatric, adult or mixed ED [1][2][3][4][5]. Authors from an English institution have found that breathing difficulty (20.1%), febrile illness (14.1%) and diarrhoea with or without vomiting (14.0%), rash (8.6%) and cough (6.7%) make up most of the medical problems among children aged 1 to 16 years presenting to the PED [1]. In contrast, the same institution reported that in adolescent patients, injury was the most frequently encountered presenting problem (71.8%).…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of paediatric presentations to the ED are steadily rising [1,2]. In comparison to other countries, there is paucity of Swiss data in the published literature on the distribution of presenting medical and surgical complaints in children who visit a paediatric, adult or mixed ED [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation